Degradabilidad y Cinética Ruminal in situ de una mezcla de ensilajes de maíz forrajero (Zea mays) y cáscara de plátano verde (Musa paradisiaca) en diferentes proporciones en una dieta base - Mejia Guadamud, Jandri Alejandro (2021)
The use of agricultural residues in the feeding of ruminants has originated a process that allows giving a management option to productive waste. In this sense, the objective of the study was to establish the in situ ruminal kinetics and degradability of forage maize silage with green banana peel residues in different proportions of a base diet. The treatments evaluated were T1=50% corn silage; 0% green banana peel, T2=45% corn silage; 5% green banana peel, T3=40% corn silage; 10% green banana peel, T4=35% corn silage; 15% green banana peel, T5=30% corn silage; 20% green banana peel. A completely randomized block design with five treatments and four replications was applied. To determine the differences in the means, Tukey's multiple range test was obtained (p<0.05). The material to be ensiled was collected at 90 days of age (Vegetative Stage V8). Banana peel residues, rice powder, soybean paste and mineral salts were used. The anaerobic fermentation process lasted 30 days, the samples were dried in a forced air oven at 65ºC for 48 hours to determine the humidity and partial dry matter, they were ground in a Thomas Willy mill with a 2 mm sieve. It was dried in an oven at 65 °C for 48 h. DISMS and DISMO are prolonged using the nylon bag technique in four castrated and rumen fistulated cattle. For each run, seven nylon bags of 10 x 21 cm and 53 mm pore size were used, each containing 10 g of ground sample, with an incubation sequence of 0, 3, 6, 12, 24, 48 and 72. hours. The in situ digestibility of DM and OM increased with the 20% inclusion of green banana peel with an effective degradation of 57.80 and 57.47% with a passage rate (k 0.02). The in situ ruminal degradability parameters of the dry matter and organic matter of forage corn silage with green banana peel residues, is a viable alternative using the 20% inclusion of green banana peel due to the dynamics of ruminal degradation of the MS and MO.